2017
DOI: 10.1111/aas.12993
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response team patients triaged to remain on ward despite deranged vital signs: missed opportunities?

Abstract: Patients triaged to stay on ward despite deranged vital signs are high-risk patients who could benefit from routine follow-up by RRT nurses before they deteriorate beyond salvation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…7 We have previously published two single centre trials investigating this subject and found that abnormal vital signs at the time of RRT arrival (whether classified as normal/abnormal according to hospital's 'track and trigger' criteria or the NEWS 20 ) were independently associated with worse outcome. 32,33 The present study confirms this observation in a large multicentre setting and contribute further specific observations across organ systems. Interestingly, RRThaemo patients were more likely to survive than RRT patients with no abnormal vital signs.…”
Section: Vital Signs Upon Rrt Arrivalsupporting
confidence: 89%
See 1 more Smart Citation
“…7 We have previously published two single centre trials investigating this subject and found that abnormal vital signs at the time of RRT arrival (whether classified as normal/abnormal according to hospital's 'track and trigger' criteria or the NEWS 20 ) were independently associated with worse outcome. 32,33 The present study confirms this observation in a large multicentre setting and contribute further specific observations across organ systems. Interestingly, RRThaemo patients were more likely to survive than RRT patients with no abnormal vital signs.…”
Section: Vital Signs Upon Rrt Arrivalsupporting
confidence: 89%
“…While most RRT studies have documented the RRT trigger reasons, data on the actual vital signs upon RRT arrival are sparsely reported. 7,32,33 The high fidelity RRTobs data captured in a structured manner by an experienced team with critical care skills warrant more study. Boniatti et al found that 30% of the RRT patients had normal vital signs upon RRT arrival.…”
Section: Vital Signs Upon Rrt Arrivalmentioning
confidence: 99%
“…Some rapid response team (RRT) patients may be incorrectly triaged to remain on wards; this leads to repeat RRT reviews and possible delays in ICU admittance/ higher morbidity [9, 10]. There are very limited data on the physiological state of the patients that s RRTs actually evaluate on general wards, although vital signs recorded during the reviews could provide important information for system-development, trans-institutional comparisons and data validation.…”
Section: Introductionmentioning
confidence: 99%
“…competence of the RRT staff, critical care capacity and local routines and traditions when assessing need for critical care. 26 Taking into consideration that many previous studies are retrospective, our results from a prospective study might suggest the need for a complementary, supportive triage tool in order to enable accurate decisions on the need for ICU admission during RRT assessments.…”
Section: Discussionmentioning
confidence: 96%
“…The ability of NEWS and NEWS 2 in this study to predict ICU admissions amongst patients assessed by the RRT was rather weak, both in absolute terms and compared to previous studies. Deranged vital signs recorded by the RRT during a review has previously been identified as an independent risk factor for 30-day mortality despite interventions of the RRT, 26 hence a timely and adequate triage of patients in need of intensive care is of vital importance. However, decisions on ICU admittance are under the influence of many factors, e.g.…”
Section: Discussionmentioning
confidence: 99%